Study of an antimicrobial starch-based active packaging system - Khairuddin, Nozieana; Mohd. Razi, Aishahtur Radhiah; Muhamad, Ida Idayu (2005)
In response to the dynamic changes in current consumer demand and market trends, the area of Active Packaging (AP) is becoming increasingly significant. An Antimicrobial Active Packaging can be made by incorporating and immobilizing antimicrobial (AM) agents into food packages and applying a bio-switch concept. By that, the mechanism of antimicrobial release between the developed bio-switch particles and the stimulus of a microbial contamination can be studied. A starch-based film was prepared and incorporated with antimicrobial agents consisting of a combination of nisin and lysozymes. This film was then inoculated with the bacteria Escherichia coli and Bacillus subtilis to carry out the microbial contamination study. The changes in film appearance that indicate microbial growth inhibitory action by the AM agents were being examined. Clear zones formed on the film appearance showed the combination of both AM agents gives good inhibition to the growth of E.coli and B.subtilis with satisfying inhibition rate. With the advent of new polymer materials and antimicrobials, the development of AP could prolong the shelf life of food and reduce the risk of foodborne illness caused by microbial contamination.